A rare case of cutaneous granular cell tumour - Arumugam, Rohini; Joseph, Leena Dennis; Venkatesan, Vidhya; Narayanan, C. D. (International Journal of Research in Medical Sciences, 2021)
Granular cell tumors are uncommon tumors of uncertain etiology. It accounts for approximately 0.5% of all soft tissue tumors. However, the involvement of skin is rare. Only few cases of cutaneous granular cell tumor is reported till date. Here, we present a case of cutaneous granular cell tumor in a 48 years female patient.